ดีออกซิจิเนชันเชิงเร่งปฏิกิริยาของน้ำมันชีวภาพในเครื่องปฏิกรณ์แบบเบดนิ่ง - วารินทร์ หาญอุดมลาภยศ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This article studied the quality improvement of bio-oil via elimination of the oxygenated compounds containing in bio-oil by catalytic deoxygenation using 1% (w/w) of nickel-molybdenum sulfide supported on gamma-alumina (1%NiMoS/γ-Al2O3) as a catalyst in a fixed-bed reactor. The effect of reaction parameters such as the bed height, reduction temperature for catalyst, reaction temperature for deoxygenation, amount of catalyst, flow rate of nitrogen gas (N2) stream and the fraction of hydrogen (H2) in the fed gas stream on the product yields, the molar ratio of oxygen/carbon and components in the gaseous product was evaluated. The result showed that the use of 20 g of catalyst reduced at 550 °C for catalytic deoxygenation at 500 °C in the presence of 60 mL/min of N2 flow rate was the optimum condition to reach the maximum level of catalytic deoxygenation. This condition could decrease the molar O/C ratio of bio-oil from 1.09 to 0.11 and the total acid number of bio-oil was also reduced from 151 to 38.4 mg KOH/g after catalytic deoxygenation. The mechanism for removal of oxygenated compounds in the bio-oil involved with carbonylation, carboxylation, dehydration, steam reforming and water-gas shift to convert oxygenated molecules as water and gaseous products such as H2, carbon monoxide, carbon dioxide and methane. The gaseous components in products were analyzed by using gas-chromatography. The chemical and simulated distillation compositions of bio-oil before and after catalytic deoxygenation were detected by using gas chromatography-mass spectrometry and simulated distillation gas chromatograph, respectively.